Peran kepuasan terhadap minat beli ulang dengan word-of-mouth sebagai mediator ada pelanggan Kopi Tuku di Jabodetabek - Herdiyanto, Robertus; Pardede, Ratlan (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
Kopi Tuku is one of the modern café brands, specifically because it’s included in the Contemporary Coffee which uses Indonesian local coffee beans. The existence of Kopi Tuku makes researchist eager to know and analyze its customers behaviors specially in Jabodetabek area. This research aims to see the effect of customer satisfaction on repurchase intention with word-of-mouth as the intervening variable. This is a quantitative research with purposive sampling method to obtain the respondents. The research data was taken using g-form questionare which was processed and tested using Structural Equation Model analysis using AMOS 21 software. The population for this research is Kopi Tuku customers in Jabodetabek area with 214 respondents as its samples. After researchist conducting the hypothesis testing, the result are(1) Satisfaction has a positive and significant effect on Repurchase Intention, (2) Satisfaction has positive and significant effect on Word-of-Mouth, (3) Word-of-Mouth has no significant effect on Repurchase Intention and (4) Satisfaction has a positive and significant effect on Repurchase Intention with Word-of-Mouth as a mediating variable. This research also put the company’s policy regarding green policy as an indicator that reflects customer satisfaction